Medical Education in the Former Soviet Union: Opportunities in Armenia. Issue 1 (13th August 2020) - Markosian, Christopher; Shekherdimian, Shant; Badalian, Samuel S.; Libaridian, Lorky; Jilozian, Ani; Baghdassarian, Aline
Medical education is a critical aspect of healthcare quality and thus requires sufficient investment to meet international standards. The Republic of Armenia, a nation that became independent of the Soviet Union in 1991, has not experienced significant advancement of its medical education system as the Western world has. In 2018, the country underwent a revolution to oust systematic corruption and transition to a true democracy, providing an opportunity for future efforts to improve medical education. The Armenian diaspora, which consists of approximately two to three times more individuals than the country's population, includes healthcare professionals who are motivated and willing to contribute to the advancement of medical education. Assessing the perspectives of stakeholders is a key first step in this endeavor. We conducted a survey of recent medical graduates in Armenia, which revealed self-awareness of deficiencies in clinical, research, and leadership skills, desire to receive further training to improve these skills, and positive attitudes toward diaspora engagement. Thus, it is critical to incorporate a coordinated effort from the diaspora in addition to the local physician workforce, educational institutions, and government to bring about improvements in medical education in Armenia.